Mulheres catadoras fotografando o mundo-vida: revelando processos educativos - Checchi, Conrado Marques da Silva de (Universidade Federal de São Carlos, 2018)
This research sought to identify, describe and understand which educative processes emerge from photography as a language that enables the communication and critical reading of the lifeworld of eleven women waste pickers, who participate in the Acácia Cooperative, in Araraquara city. Taking as a starting point the methodological coexistence in the activities carried out by the group during the door-to-door allocation of residences, an intervention was made to distribute digital cameras to take wherever they wanted and to create photographs with the following question: What is it for you, pick waste solidary? From the photographs were conducted individual interviews and three dialogue circle about the photographs created by each participant, seeking to reveal educational processes that emerge from the dialogue of each collector about his photographs, and then with they all like a group of womans waste pickers. The methodology used for this qualitative research was based on a phenomenological method focusing on the situated phenomenon. The analysis of the data revealed different educative processes that permeate the practice of picking recyclable waste materials, which present the senses cultivated within the social practice and that are present in the life of the different womans waste pickers, announcing, with this, the dense plots in which are inserted and that reveal transforming looks, of overcoming obstacles and adversities present in the chain of recycling and that fall mainly on the womens recyclable pickers. The comprehension of the meanings elaborated by collectors through the photographic act, involves understanding them in exteriority to the hegemonic system, positioning with them, so that the perception of the image is not limited to its surface, thus requiring another epistemology, based on the otherness and the recognition of liberation struggles in the face of Western modernity. Like windows, the images seeks to illuminate the vision, provoking reflections on the lived times and opening a gap in the representations that the city gives to the lives of these womens. Through this intervention we seek to help the group of women pickers in the constant practice of collective construction that they carry out in the self-management and solidarity, the principles of their organization.
Womens waste pickers photographing the lifeworls: revealing educative processes
Keywords: Processos educativos; Fotografia; Mulheres catadoras; Educative processes; Photograph; Women waste pickers; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM